Digital Advertising Fraud: Detection and Mitigation Strategies - Tewari, Poorna Gautam (Journal of Global Economy, Business and Finance, 2026)
Digital advertising has witnessed exponential growth in recent years, becoming a significant part of modern marketing strategies. However, this surge in digital advertising expenditure has also attracted fraudulent activities that exploit vulnerabilities in the ecosystem. This article aims to explore various types of digital advertising fraud and provide insights into the preventive measures that can be taken to mitigate their impact. Through an extensive review of existing literature and industry reports, this study highlights the importance of proactive strategies to combat digital advertising fraud and protect advertisers' investments.